Решите уравнение:
а)3(-2х+1)-2(x+13)=7x-4(1-x),
б)-4(5-2а)+3(а-4)=6(2-а)-5а
в)3у(4у-1)-2у(6у-5)=9у-8(3+у)
г)15х+6х(2-3х)=9х(5-2х)-36.
Заранее спасибо!!!

2

Ответы и объяснения

2013-12-26T20:01:04+04:00
Г)15х + 12х -18х(квадрат)=45х - 18х(квадрат) - 36
15х+12х-18х(квадрат)- 45х + 18х(квадрат) +36= 0
-18х=-36
х= 2
к нулю можно не приравнивать,а сразу сокращать
2013-12-26T20:04:08+04:00
А)3(-2х+1)-2(x+13)=7x-4(1-x),
   - 6х +3 -2х - 26 = 7х - 4 + 4х
  -6х - 2х -7х -4х = -4 -3 +26
  -19х =  19
   х = -1

б)-4(5-2а)+3(а-4)=6(2-а)-5а
   -20 + 8а + 3а -12 = 12 -6а  - 5а
  8а + 3а +6а +5а = 12 +20 +12
   22а =  44
    а =  2
в)3у(4у-1)-2у(6у-5)=9у-8(3+у)
   12уКвадр - 3у - 12у квадр +10 = 9у -24 - 8у
-3у -9у +8у = -24 -10
 -4у = -34
  у = 8,5
 
 г)15х+6х(2-3х)=9х(5-2х)-36.
   15х + 12х - 18х квадр = 45х  - 18хквадр -36
  15х +12х -45х = -36
 -18 х = -36
 х = 2